The Implementation Analysis of Intellectual Capital to Department Performance in Padang State University - sulastri, Sulastri; Andriani, Chichi; Fitria, Yuki (APMBA (Asia Pacific Management and Business Application), 2014)
The purpose of this research was to observe the effect of the age of the organization department in Padang State University on performance through human capital, structural capital and relational capital. The sample is all of department in Padang State University, which is 33 departments. The data were collected through questionnaires and analyzed using partial least squares (PLS). The results showed that the age of the department is not direct and significant impact on the department performance. While the age departments significantly affect the department's human capital, structural capital and relational capital. Furthermore, the human capital, structural capital and relational capital significantly positive affect the department performance. This research failed to prove the existence of variable human capital, structural capital and relational capital as a mediating variable but serves as an intervening variable. Its means that age of department performance cannot determine performance without increasing the human capital, structural capital and relational capital.